THU0386 Aphaeretic Procedures and Intravenous Immunoglobulins in Addition to Conventional Therapy to Treat Pregnant Women with High-Risk Antiphospholipid Antibody Syndrome. A Prospective Cohort Study. (9th June 2015) - Ruffatti, A.; Favaro, M.; Zambon, A.; Tonello, M.; Del Ross, T.; Calligaro, A.; Hoxha, A.; Nardelli, G.B.; Punzi, L.
Abstract : Background: Conventional treatments based on the use of low molecular weight heparin (LMWH) and/or low dose aspirin (LDA) fail in about 20-30% of pregnant women affected with antiphospholipid antibody syndrome (APS). Several risk factors predictive of pregnancy failure during conventionally treated pregnancies have been identified. It has recently been reported that APS women with thrombosis and triple aPL positivity have significantly higher live birth rates when they are prescribed an additional second-line therapy (1). There are as yet no guidelines on the optimal additional treatment strategy for APS women at high risk of pregnancy failure. Objectives: This prospective cohort study was undertaken to investigate the efficacy and safety of a second-line treatment protocol administered in addition to conventional therapy to pregnant women with high-risk APS. Methods: Seventeen pregnancies in 13 women, all diagnosed with primary APS on the basis of the Sydney International Consensus Statement classification criteria, were assessed perspectively. The study's inclusion criteria were: presence of triple aPL positivity (IgG/IgM anticardiolipin plus IgG/IgM anti-β2Glycoprotein I antibodies plus lupus anticoagulant) along with a history of thrombosis and/or of one or more severe pregnancy complications (preeclampsia, HELLP syndrome, placental insufficiency). The treatment protocol included weekly aphaeretic procedures i.e. plasmapheresis or immunoadsorption and fortnightly 1g/kg intravenous immunoglobulins (IVIG) in addition to daily LDA and twice daily LMWH throughout pregnancy. Results: Seventeen consecutive pregnancies occurring between 2002 and 2014 in 13 primary APS patients were assessed. All had triple aPL positivity. Seven (53.8%) had a history of thrombosis, 2 (15.4%) reported one or more severe pregnancy complications and 4 (30.8%) had both. Prior to the study none of the 13 women had experienced a normal pregnancy; nine (69.2%) reported one or more unsuccessful pregnancies while treated with conventional therapy. Of the 17 pregnancies treated conventionally together with the second-line therapy, 16 (94.1%) had favorable outcomes producing 16 live infants, all born between the 26th and 37th week (mean 33.4±2.7 SD). Three (23.1%) women had multiple pregnancies. The infants (8 males and 8 females) had a mean birth weight of 41.9 percentiles ±23.3 SD (range 10-97). The mean Apgar score at 5 min was 8.4±1.0 SD (range 6-10). Due to severe preeclampsia one pregnancy (5.9%) ended at the 24th week; the premature neonate died during the perinatal period. Maternal complications were noted in 4 cases (25%) and foetal complications in 4 (25%). No side-effects linked to the various types of therapy included in the treatment protocol were registered. Conclusions: In view of the high live birth rate and the safety of the treatment noted in these women, we can conclude that additional aphaeretic procedures and IVIG should be considered when high-risk pregnancies are being evaluated for treatment. References: Ruffatti A, et al. Thromb Haemost 2014; 112: 727-735. Disclosure of Interest: None declared